Credit default swaps : mechanics and empirical evidence on benefits, costs, and inter-market relations /: mechanics and empirical evidence on benefits, costs, and inter-market relations. (2018) - Culp, Christopher L; Van der Merwe, Andria; Stärkle, Bettina J
No abstract available